Examining supply chain management practices at Karoi District Hospital - Zulu, Tapiwa A (Midlands State University, 2020)
Supply chain management is a crucial aspect in the operations of an organisation. Supply chain management is a multidimensional study that can yield a number of results to an organisation. The research study examined the supply chain management practices at Karoi District Hospital. In this study supply chain management (SCM) practices were being examined to see their effects on the overall performance of the hospital. It was conceptualized that SCM practices positively affects organizational performance. This was guided by these objectives: to determine the influence of strategic supplier partnership on organizational performance, to assess the influence of information sharing in supply chain, to determine the impact of improved record management in the supply chain on the performance of the organisation and to examine the contribution of supply chain (internal) lean practices on organizational performance. This was a census survey and a descriptive research design was used. Data was collected by administering 48 questionnaires to different categories of employees at KDH. Mean and Cumulative Frequencies were used to analyze the data. Tables, graphs and charts were used to present research findings. Study findings showed that there is a positive linear relationship that exists between supply chain management practices and organizational performance. The study recommends internal and external collaborations to ensure long term relations, simple and detailed records to be kept and training of the procurement and logistics staff to ensure easy transition to new technology.